Dose Reduction/Discontinuation of Antipsychotic Drugs in Psychosis; Effect on Cognition and Functional Outcomes - Omachi, Yoshie; Sumiyoshi, Tomiki (Frontiers in Psychiatry, 2018)
Backgrounds There is a debate regarding the optimal timing of discontinuation of antipsychotics in patients with first episode psychosis (FEP) or schizophrenia. We aim to provide a review of the literature on which strategy (medication maintenance vs. dose reduction/discontinuation) is more likely to maximize outcomes, such as cognition and social function. Methods Using PubMed, the Cochrane Library and systematic reviews, articles published between 2007 and 2018 were reviewed, which investigated the effect of dose reduction/discontinuation compared with maintenance treatment on measures of cognition and/or social function in FEP and schizophrenia. Results Six studies were identified; 2 studies reported on cognition and 4 studies on social function. All studies except one reported the improvement of functional outcomes in remitted patients with FEP or schizophrenia allocated to a dose reduction/discontinuation arm was equal to or better than that in patients for whom medication doses were maintained. One trial of social function with a 1-year follow-up period found a greater improvement in the medication maintenance group, while no group difference was observed with 3-year and 10-year follow-up period. On the other hand, a 7-year follow-up study observed a superiority for the dose reduction/discontinuation regimen in terms of social outcome. Two studies on cognition with a short follow-up period reported a greater improvement for the dose reduction/discontinuation group. Conclusions Information on cognition and social function has been relatively sparse. These measures of functional outcome should be considered in deciding which strategy of antipsychotic treatments is beneficial in individual cases with FEP or schizophrenia.